2011
DOI: 10.1007/s10551-011-0872-3
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal Behaviors Syndrome: An Ethical Perspective

Abstract: absence, distributive justice, ethical climate, ethical perceptions, intent to leave, lateness, nurses, organizational commitment, organizational justice, withdrawal behaviors,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 116 publications
(153 reference statements)
0
23
0
Order By: Relevance
“…Caring climate influences withdrawal behaviours such as intent to leave (Shapira‐Lishchinsky & Even‐Zohar, ) or calling in sick (Peterson, ) that occur when employees feel that the organization cares nothing about their welfare. Studies of sports teams have shown that caring climates may enhance psychological well‐being among members (Fry et al ., ), encourage more involvement in sports, and keep more athletes from dropping out (Fry & Gano‐Overway, ).…”
Section: Introductionmentioning
confidence: 99%
“…Caring climate influences withdrawal behaviours such as intent to leave (Shapira‐Lishchinsky & Even‐Zohar, ) or calling in sick (Peterson, ) that occur when employees feel that the organization cares nothing about their welfare. Studies of sports teams have shown that caring climates may enhance psychological well‐being among members (Fry et al ., ), encourage more involvement in sports, and keep more athletes from dropping out (Fry & Gano‐Overway, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, nurse absenteeism burdens the department's staff, especially when a replacement is not found. Additionally, nurses who intend to leave their position are not motivated and as a result are not effective (Shapira‐Lishchinsky & Even‐Zohar, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In new theoretical formulations, the focus in two components of independence and instrumental tendencies is on oneself instead of others, and reliance is on personal beliefs instead of on group values, thus, they are considered among components of tendency toward personal ethics (Grant and Patil, 2012). In terms of nature, each one of the components of organizational ethical climate has specific behavioral, cognitive, and emotional outcomes for employees (Woodbine, 2006;Shapira-Lishchinsky and Even-Zohar, 2011;Ünal, 2012;Zehir et al, 2012;Wang and Hsieh, 2012). The two important outcomes of components of organizational ethical climate, focused on in this study, are organizational empathy and civic virtue.…”
Section: Organizational Ethical Climatementioning
confidence: 99%